Québécois French in U.S. Academia: Overcoming Challenges and Creating Opportunities. (January 2016) - Bosworth, Yulia
Abstract : This article discusses the status of Québécois French in U.S. academia in light of longstanding challenges and changes presently underway in U.S. French education. The presentation of Québécois French in U.S. university classrooms has traditionally taken place in a context shaped by normative pedagogy, France-centeredness, and a curricular dominance of literary studies. The negative perception of this language has been exacerbated by widespread linguistic misconceptions and misrepresentations on the one hand, and by a negative sociolinguistic self-image of the Québécois, on the other. The main objective of this work is to demonstrate that recent trends in French education constitute a favorable climate in which to overcome these challenges and create opportunities to promote Québécois French as a legitimate object and medium of French study. Specifically, the article presents evidence of the shift in student curricular interests away from literary studies and the declining monopoly of France and its high culture in the consciousness of our students. Additionally, the new linguistic self-perception in Quebec and the acceptance of Standard Québécois French, further reinforce the positive environment for the promotion of Québécois French in U.S. academia. An emphasis is placed on the critical role of faculty in influencing students' attitudes in toward Québécois French and its culture.